Samarium oxide and samarium oxynitride thin film gate oxides on silicon substrate / Goh Kian Heng - Goh, Kian Heng (2017)
Sputtered pure samarium (Sm) metal films on silicon substrates were thermally oxidized and oxynitrided at various temperatures (600 – 900 °C) and durations (5 – 20 min). Effects of thermal oxidation ambient in oxygen (O2) and nitrous oxide (N2O) gas ambient on the physical and electrical properties of samarium oxide (Sm2O3) and samarium oxynitride (SmxOyNz) thin films were investigated. For all samples oxidized in O2, the XRD patterns showed that crystallinity did not increase with oxidation duration. The crystallinity of Sm2O3 increased as the oxidation temperature increased. Two interfacial layers were observed in high resolution transmission electron microscopy (HRTEM) cross sectional images. The existence of semi-polycrystalline interfacial layers was supported by X-ray diffraction (XRD), Fourier transform infrared (FTIR), Raman analysis, and energy dispersive X-ray (EDX) spectroscopy composition analysis. The activation energy or growth rate of each stacked layer was calculated from Arrhenius plots. A physical model related to semi-polycrystalline interfacial layer is proposed and explained. The smoothest surface of the 700 °C sample showed the best current-voltage (I-V) characteristic. For thermal oxidation in O2, the optimum parameters of oxidation temperature and duration were 700 °C and 15 min, respectively. The optimized sample yielded the best electrical properties with the lowest leakage current (1.15 x 10-4 A cm-2 at 0.71 MV cm-1), highest electrical breakdown field (0.71 MV cm-1), highest barrier height value (2.12 eV), highest trap energy (7.485 x 10-4 eV), lowest trap density (6.88 x 1021 cm-3), highest effective dielectric constant (214), lowest effective oxide charge (2.81 x 1013 cm-2), lowest slow trap charge density (5.56 x 1012 cm-2), lowest average interface trap density (~ 1014 eV-1 cm-2), and lowest total interface trap density (7.31 x 1013 cm-2). For all the samples oxynitrided in N2O, polycrystalline SmxOyNz was formed. Amorphous Sm-silicate (SmaSibOcNd) was embedded between the SmxOyNz film and the Si substrate. The crystallinity of Sm2O3 increased when the oxynitridation temperature increased from 600 ºC to 700 ºC but decreased as the oxynitridation temperature increased to 900 ºC. The weak intensities of Sm2O3 were also detected in FTIR and Raman analysis. According to HRTEM cross sectional images and EDX compositional analysis, only one interfacial layer (SmaSibOcNd) was formed. Similarly, the activation energy or growth rate of each stacked layer was calculated from Arrhenius plots. A physical model related to formation of semi-polycrystalline SmxOyNz thin film and amorphous SmaSibOcNd interfacial layer is suggested and explained. The sample oxynitrided at 700 ºC for 15 min exhibited the best electrical properties with the lowest leakage current (9.54 x 10-7 A cm-2 at 3.9 MV cm-1), highest electrical breakdown field (3.9 MV cm-1), barrier height value (6.33 eV), highest trap energy (0.005 eV), and lowest trap density (5.657 x 1021 cm-3). By comparing the optimized parameters (700 ºC and 15 min) of both oxidized and oxynitrided samples, it showed that the electrical performance is improved by incorporation of nitrogen. The high valance vacancy of nitrogen acts as network former hence stabilizing the oxynitrided structures.